Beyond diagnosis: the relevance of social interactions for participation in inclusive preschool settings. (18th August 2019) - Pinto, Ana I.; Grande, Catarina; Coelho, Vera; Castro, Susana; Granlund, Mats; Björck-Åkesson, Eva
ABSTRACT: Purpose: This study aims to explore the role of three specific factors within the child–environment interaction process – engagement, independence and social interactions – in influencing development and learning of children with disabilities in inclusive preschool settings. The main question is whether children can be categorised in homogenous groups based on engagement, independence and social interactions (proximal variables within a biopsychosocial framework of human development). The study also examined whether children with the same diagnosis would group together or separately, when trying to identify clusters of engagement, independence and social interactions, and additionally whether such clusters vary as a function of individual child characteristics, and/or as a function of structural and process characteristics of preschool environment. Methods: Data was taken from an intervention study conducted in mainstream preschools in Portugal. A person-centered cluster analysis was conducted to explore group membership of children with various diagnoses, based on their engagement, independence and social interaction profiles. Results: Results show that children clustered based on similarity of engagement, independence and social interaction patterns, rather than on diagnosis. Besides, it was found that quality of peer interaction was the only predictor of cluster membership. Conclusion: These findings support the argument that participation profiles may be more informative for intervention purposes than diagnostic categories, and that preschool process quality, namely peer interaction, is crucial for children's participation.